What can we expect from precision asteroseismology?. Issue Volume 9:Issue S301(2013) (18th February 2014) - Handler, G.
Abstract: Precision asteroseismology is the determination of accurate stellar parameters from oscillation data. At first successful for pulsating white dwarf stars, it is now applied to more and more types of stars. We give a number of selected examples where precision asteroseismology, but also asteroseismology based on few observables may lead to considerable improvement of stellar astrophysics in the near future.